2021
DOI: 10.3390/ma14081902
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Durability of Lime-Cement Mortars Prepared with Water Containing Micro-Nano Bubbles of Various Gases

Abstract: The paper presents the experimental studies on the effect of the water containing micro-nano bubbles of various gases on the physico-mechanical properties of lime-cement mortars. In total, 7 types of mortars were prepared: with water containing the micro-nano bubbles of O2, O3 or CO2 as 50% or 100% substitute of ordinary mixing water (tap water) and the reference mortar prepared using tap water. In order to determine the influence of water with micro-nano bubbles of gases, the consistency of fresh mortar and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
4
11
0
Order By: Relevance
“…A previous study by the authors [36] showed a 1.9% increase in water absorption by weight for lime-cement mortars containing water with micro-nano ozone bubbles compared to a reference mortar. Micro-nano gas bubble water also improves cement composites in terms of mechanical properties.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…A previous study by the authors [36] showed a 1.9% increase in water absorption by weight for lime-cement mortars containing water with micro-nano ozone bubbles compared to a reference mortar. Micro-nano gas bubble water also improves cement composites in terms of mechanical properties.…”
Section: Introductionmentioning
confidence: 73%
“…The described configuration allowed for obtaining typical nanobubble diameters from 80 to >200 nm [36]. The size and quantity of micro-nano bubbles were controlled by such physical parameters as liquid and gas flow rates, as well as pressure.…”
Section: Methods Of Obtaining Micro-nano Gas Bubblesmentioning
confidence: 99%
See 2 more Smart Citations
“…Its advantage is that it does not require only quantitative type data. In the past, the method has been used in work on contaminants in the water environment [35,36], the effect of water on the physical properties of concrete [37], but also haptic analysis of physical measurements of roughness and compressibility of materials [38].…”
Section: Statistical Elaboration Of Research Resultsmentioning
confidence: 99%